Old Babylonian religious poetry in Anatolia: From solar hymn to plague prayer - Metcalf, C (De Gruyter, 2015)
In a recently published Old Babylonian Sumerian solar hymn, a diseased supplicant inquires into the nature of a past but unknown religious offence with which he has angered his personal god. The present article contains an interpretation of this passage and a discussion of its various Hittite versions, which range from an almost literal translation (in the Prayer of Kantuzili) to renderings that were strongly adapted to Hittite customs (in the prayers of Mursili II.). This unusually well-documented case offers new insights into the translation and adaptation of literary texts in the ancient Near East.